2019
DOI: 10.1186/s12913-019-3967-7
|View full text |Cite
|
Sign up to set email alerts
|

Need analysis for a new high acuity medical psychiatry unit: which patients are considered for admission?

Abstract: Background The study aims were: to estimate the proportion of patients with an indication for admission to a new high acuity Medical Psychiatric Unit (MPU), to explore the reasons for MPU-admission according to different health disciplines, and to check for differences in patient characteristics. The results of this study are to be utilized in the proposed establishment of a high-acuity MPU in a University Medical Center. Such a unit currently does not exist at Erasmus MC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“… 42 Primary care medical specialists and psychiatrists work closely together at these units. Caarls et al 23 found that MPUs in general are the most effective in providing care for high-level psychiatric and medical patients with complex conditions in particular. Previous studies described a gap between managers and nonmanagers concerning mission statements in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 Primary care medical specialists and psychiatrists work closely together at these units. Caarls et al 23 found that MPUs in general are the most effective in providing care for high-level psychiatric and medical patients with complex conditions in particular. Previous studies described a gap between managers and nonmanagers concerning mission statements in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for setting up such a unit fall into several categories and are similar to the reasons why an MPU in Erasmus MC (Rotterdam, The Netherlands) was recently established: (1) managing the increasing complexity and behavior that is disruptive to physical treatment in an aging and more often multimorbid population, (2) improving the quality of care, and (3) the promise of cost-effectiveness by reducing length of stay and readmissions. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Type 4 relates to high psychiatric/high medical acuity units or portions of medical units that provide high acuity medical/psychiatry care. Caarls et al (2019) discussed the concept of acuity in the context of the complexity of psychiatric and medical needs without defining acuity. Howver (2014) developed the Vanderbilt acuity tool for nurses to assess acuity, establish the required care level, and appropriately utilize resources.…”
Section: Psychiatric Acuitymentioning
confidence: 99%
“…Anders in den USA [3], wo steigende Gesundheitskosten und eine Reform der medizinischen Ausbildung seit den 1930er Jahren zu einer schrittweisen Rückkehr der Psychiatrie in den "medizinischen Mainstream" führten. Heute gibt es dort etwa 1700 psychiatrische Einheiten an Allgemeinkrankenhäusern, teils in Form spezialisierter Einrichtungen für komorbid erkrankte Patienten [23]. In Deutschland ist ein Zusammenwachsen von somatischer Medizin und Psychiatrie mit der Psychiatrie Enquete der 1970er Jahre verbunden.…”
Section: Psychiatrische Stationen An Allgemeinkrankenhäusern -Historische Entwicklungunclassified